The role of specialized prevention clinics for the short term follow-up of acute coronary syndromes - Salih Kılıç; Evrim Şimşek; Hatice Soner Kemal; Elif İlkay Yüce; Cüneyt Türkoğlu; Meral Kayıkçıoğlu (KARE Publishing, 2017)
Objective: This study aimed to investigate the effect of specialized prevention clinics and standard clinics follow-ups on secondary protection after acute coronary syndrome (ACS) on cardiovascular risk factors. Methods: A total of 118 patients who received thrombolytic therapy after being diagnosed with ST-segment elevation myocardial infarction were followed up for 6 months. After ACS, patients in a specialized prevention clinic (Group 1) (n=67) and those in a standard clinic (Group 2) (n=51) were compared in terms of the change in their lifestyle, management of risk factors, and drug compliance. Results: No significant difference was found between groups in terms of baseline clinical and laboratory findings except for triglyceride level (Group 1: median 174 mg/dL; Group 2: median 136 mg/dL; p=0.039). Six months after indexing, smoking cessation (72.4% vs. 50%, p=0.037), diet compliance (43% vs.19.6%, p=0.012), and exercise rates (31% vs. 13.7%, p=0.044) were significantly higher in Group 1. Although the weight control rate was higher in Group 1, no significant difference was noted between the groups (27% vs. 15.6%, p=0.219). The rate of systolic and diastolic blood pressures >140/90 mm Hg was significantly higher in Group 2 (23.5% vs. 9%, p=0.029) at 6 months. The median low-density lipoprotein cholesterol (LDL-C) value was significantly lower in Group 1 patients (Group 1: 91 mg/dL; Group 2: 102 mg/dL; p=0.042). Moreover, the rate of LDL-C ≤70 mg/dL or ≥50% reduction compared with baseline was significantly higher in Group 1 (32.8% vs. 13.7%, p=0.016). Although the recommended treatments were similar in both groups, the statin use rate was significantly higher in Group 1 (95.5% vs. 80.3%, p=0.021) at 6 months. Conclusion: The results of the study showed that specialized prevention clinics were more effective during the management of cardiovascular risk factors after ACS.